2018
DOI: 10.1177/0361198118774184
|View full text |Cite
|
Sign up to set email alerts
|

Signal Priority Request Delay Modeling and Mitigation for Emergency Vehicles in Connected Vehicle Environment

Abstract: Connected vehicle-based signal priority control is widely regarded as an advanced method for improving travel efficiency of an emergency vehicle when passing through intersections. However, the vehicle-to-everything (V2X) communication delay is a critical factor affecting the performance of signal request and has rarely been considered in existing studies. This paper conducted a comprehensive delay analysis of the preemption signal request and its influence on practical preemption control for the emergency veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This section provides evaluations and results analysis. First, field implementations were conducted in a typical arterial scenario using the existing ACTIVE testbed ( 28 ). Both vehicle and infrastructure data were collected and used to analyze performances of the CV-based signal coordination prototype qualitatively.…”
Section: Evaluations and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…This section provides evaluations and results analysis. First, field implementations were conducted in a typical arterial scenario using the existing ACTIVE testbed ( 28 ). Both vehicle and infrastructure data were collected and used to analyze performances of the CV-based signal coordination prototype qualitatively.…”
Section: Evaluations and Analysismentioning
confidence: 99%
“…In Figure 5, three types of data were captured as inputs: 1) BSM data obtained from an OBE equipped on the test vehicle, 2) SPaT data, and 3) offset data recorded using the existing ACTIVE CV pilot, in Edmonton, Canada ( 28 ).…”
Section: Evaluations and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Statistics have shown that slow response to emergency calls increases the casualty rate of the victims. Fogue et al (4) and Li et al (5) cited that 10% of casualties occur within just a few minutes or seconds after crashes. The survival rate of a patient is reduced by 7% to 10% with every elapsed minute (6).…”
mentioning
confidence: 99%